NATIONWIDE ANALYSIS OF THE IMPACT OF NAFLD ON CLINICAL OUTCOMES IN IBD PATIENTS. (21st January 2021) - Noorian, Shaya; Jeon, Yejoo; Nguyen, Minh Thu; Sauk, Jenny; Limketkai, Berkeley
Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is the fastest growing cause of chronic liver disease among patients with inflammatory bowel diseases (IBD). Studies have suggested that patients with IBD develop NAFLD with fewer metabolic risk factors than those without IBD. Data have also suggested associations between NAFLD and factors inherent to IBD such as disease activity, disease duration, and prior IBD surgery. Despite this complex relationship, the impact of NAFLD on clinical outcomes in IBD patients has not been examined on a large scale. Methods: We performed a propensity-score matched study among hospitalized IBD patients using the Nationwide Readmissions Database from 2016–2017. ICD-10 codes were used to identify patients with IBD, NAFLD, and comorbidities. Patients with NAFLD were matched to those without NAFLD based on the following variables: age, sex, IBD type, metabolic syndrome (MS), and diabetes mellitus (DM). Cox regression was used to evaluate the primary outcomes of interest: readmission and death. Linear regression was used to evaluate healthcare utilization, including length of stay (LOS) and cost of care (COC). Multivariable models accounted for matched variables and adjusted for hospital characteristics, source of payment, patient income, and elective status of admissions. Statistical analyses accounted for the complex survey design. Results: The prevalence of NAFLD in all hospitalized Crohn's disease (CD) and ulcerative colitis (UC) was 2.4% and 2.1%, respectively. After matching based on predetermined variables, 11, 497 patients with CD and 6, 120 patients with UC were included in our study. NAFLD was associated with a higher risk of readmission for both CD (HR 1.93, 95% CI 1.93–2.12, p<0.001) and UC (HR 1.92, 95% CI 1.63–2.25, p<0.001). No significant association was noted between NAFLD and death in CD (HR 1.59, 95% CI 0.86–2.94, p=0.141) or UC (HR 1.42, CI 0.68–2.97, p=0.35). For healthcare utilization, NAFLD was associated with a longer LOS by 0.69 days (95% CI 0.25–1.13 days, p=0.002) and 0.82 days (95% CI 0.31–1.32 days, p=0.002) in CD and UC respectively. Additionally, NAFLD was associated with a 7, 322 higher COC (95% CI 2, 295–12, 349, p<0.01) in CD and 11, 272 (95% CI 4, 155–18, 388, p=0.02) in UC. Conclusions: NAFLD is associated with higher readmission rates, longer lengths of stay, and higher costs of care in IBD patients. Identification and management of metabolic factors should be considered in the care of patients with IBD and future research should elucidate the roles of non-metabolic factors in the development of NAFLD, given the large impact of NAFLD on clinical outcomes in IBD.